Immunogenicity and safety of 13-valent pneumococcal conjugate vaccine in HIV-infected adults in the era of highly active antiretroviral therapy: analysis stratified by CD4 T-cell count - Joon Young Song; Hee Jin Cheong; Ji Yun Noh; Min Joo Choi; Jin Gu Yoon; Woo Joo Kim (Taylor & Francis Group, 2020)
HIV-infected patients are 30- to 100-fold more susceptible to invasive pneumococcal diseases than are healthy adults. Pneumococcal vaccination may be the best way to decrease the large pneumococcal disease burden, but the optimal timing of vaccination is still unclear. In this study, HIV-infected subjects aged ≥18 years were recruited and divided into 2 age-matched groups: group 1 (subjects with CD4 T-cell count ≥350 cells/µL) and group 2 (CD4 T-cell count <350 cells/µL). Multiplex opsonophagocytic killing assay was used to compare immunogenicity after immunization with 13-valent pneumococcal conjugate vaccine (PCV13). Among 70 subjects, 67 (group 1, N = 34; group 2, N = 33) were available for the assessment of immunogenicity and safety. With respect to the post-vaccination geometric mean titer (GMT) ratios, the non-inferiority criteria were not met. Post-vaccination GMTs were significantly lower in group 2 compared to group 1 for all 4 pneumococcal serotypes (5, 6B, 18C, and 19A) tested. PCV13 was safe and well tolerated in HIV-infected patients irrespective of immune status. In conclusion, PCV13 showed significantly inferior immunogenicity among HIV-infected patients with CD4 T-cell count <350 cells/µL compared to those with a higher CD4 T-cell count.